An analytical reasoning framework for visual analytics representation - Ya’acob, Suraya (2021)
Analytical Reasoning is the foundation of visual analytics, assisted via interactive and dynamic visualization representation. The main concern of visual analytics is the analytics process itself, it is important to facilitate the human mental space during the analysis process by embedding the analytical reasoning in the visual analytics representation. This paper aims to introduce and describe the essential analytical reasoning features within visual analytics representation. The framework describes analytical reasoning features from three parts of visual analytics representation which are higher-level structure, interconnection and lower-level structure. For higher-level structure, we proposed the features of big picture, analytics goal and insights through storytelling to ensure the analytics output becomes knowledge and applicable to facilitate the business decision. For interconnection, the features of trend, pattern and relevancy induce a relationship between higher and lower-level structures. Finally, analytical reasoning features for lower-level structure are quite straightforward which are benchmarking, ranking, decluttering, clueing and filtering. It is hoped that this framework could help to shed some light in terms of understanding analytical reasoning features that can facilitate the business decision.